A preliminary study of steam and water flow in venturi tubes - Smith, R. V., author; Wergin, P. C., author; Ferguson, J. H., author; Jacobs, R. B., author; Colorado State University, publisher (Colorado State University. Libraries, 1960)
This is a report of an exploratory study of low quality steam and water mixtures flowing in a Venturi tube. Analysis of the experimental results indicate the flow pattern may be tending to change from separated, slugging flow at the entrance to annular flow at the throat. Correlations indicate the Venturi may be calibrated for use as a quality meter if the mass flow rate is known.
CER60RVS47.
September 1960.
Keywords: Venturi tubes -- Measurement